Pendampingan Pembuatan Tempat Sampah Otomatis Untuk Mendukung Kebersihan Kantor Desa Gelanggang - Fathurrahman, Imam; Djamaluddin, Muhammad; Hamzan Ahmadi; Siti Quthrotunnada; M.Yazid; Muh. Fathin Kautsar; Ira Ayu Sekar Dadu (Universitas Hamzanwadi, 2025)
Environmental cleanliness is a key factor in creating a comfortable and productive work atmosphere. This article discusses the implementation of an Arduino-based automatic trash bin at the Gelanggang Village Office as an innovative solution to support more efficient waste management. The system was designed using an ultrasonic sensor to detect objects and a servo motor to open and close the lid automatically, minimizing direct user contact. Test results show a detection accuracy of up to 95% with a fast response rate, while field observations recorded a 30% increase in proper trash disposal behavior compared to previous conditions. This implementation not only improved cleanliness awareness in the office environment but also has the potential to be applied in other public spaces such as schools and community facilities. Further development is recommended through integration of features such as a full-bin indicator and IoT-based real-time monitoringEnvironmental cleanliness is a key factor in creating a comfortable and productive work atmosphere. This article discusses the implementation of an Arduino-based automatic trash bin at the Gelanggang Village Office as an innovative solution to support more efficient waste management. The system was designed using an ultrasonic sensor to detect objects and a servo motor to open and close the lid automatically, minimizing direct user contact. Test results show a detection accuracy of up to 95% with a fast response rate, while field observations recorded a 30% increase in proper trash disposal behavior compared to previous conditions. This implementation not only improved cleanliness awareness in the office environment but also has the potential to be applied in other public spaces such as schools and community facilities. Further development is recommended through integration of features such as a full-bin indicator and IoT-based real-time monitoring